New tryphosine amphipods from Australian waters (Crustacea, Amphipoda, Lysianassoidea, Lysianassidae, Tryphosinae) - Lowry, J. K.; Kilgallen, N. M. (Zootaxa, 2014)
We report seven tryphosine genera (two new) from Australian waters for the first time and describe 13 new species: Cedrosella cito sp. nov.; Lysianella lui sp. nov.; Lysianella moonamoona sp. nov.; Microlysias soela sp. nov.; Paralysianopsis capricornia sp. nov.; Paralysianopsis dandenong sp. nov.; Paralysianopsis pomona sp. nov.; Paralysianopsis ruffoi sp. nov.; Patonga nona gen. nov., sp. nov.; Tasmanosa tasman gen. nov., sp. nov.; Tasmanosa toogooloo sp. nov.; Tryphosites colmani sp. nov.; Tryphosites psittacus sp. nov. Rhinolabia is considered to be a junior synonymy of Paralysianopsis. Paralysianopsis elliotti (Lowry & Stoddart, 1995b) and P. cf. jebbi (Lowry & Stoddart, 1995b), previously known from Papua New Guinea are also reported from eastern Australia. The type species of each genus is also catalogued and illustrated.